Financial dollarization: the role of banks and interest rates - Henrique S. Basso; Oscar Calvo-Gonzalez; Marius Jurgilas (European Central Bank (ECB), 2007)
This paper develops a model to explain the determinants of financial dollarization. Expanding on the existing literature, our framework allows interest rate differentials to play a role in explaining financial dollarization. It also accounts for the increasing presence of foreign banks in the local financial sector. Using a newly compiled data set on transition economies we find that increasing access to foreign funds leads to higher credit dollarization, while it decreases deposit dollarization. Interest rate differentials matter for the dollarization of both loans and deposits. Overall, the empirical results lend support to the predictions of our theoretical model.
Keywords: 330; Financial Dollarization; Foreign Banks; Interest Rate Differentials; Transition Economies; Finanzmarkt; Währungssubstitution; Internationale Bank; Zinsstruktur